Wireless energy monitoring system using Zigbee - Luah, Shi Qin. (2013)
This report describes the Final Year Project done by a final year student in Nanyang Technological University. The project ultimately aims to craft a Wireless Energy Monitoring System (WEMS) using low-power devices (i.e. Jennic Wireless communication sensor and controller boards). It will comprise of a database created on the internet server and a data link set up from a Power Meter (Schneider Electric Power Meter PM710) to a Personal Computer.